Designing positive, negative and standard gates for ternary logics using quantum dot cellular automata. (May 2020) - Kamali, Seyede Fateme; Tabrizchi, Sepehr; Mohammadyan, Somaye; Rastgoo, Morteza; Navi, Keivan
Abstract: Quantum dot cellular automata (QCA) is one of the promising alternatives for computer circuit design. In this technology cell size is significantly reduced as well as the power dissipation and the chip area. It is possible to design efficient multiple-valued logic circuits using this technology. Theoretical aspects of ternary QCAs (tQCA) are developed and the feasibility of applying these elements is studied. In this paper, we present Negative AND (N-AND), Negative OR (N-OR), Positive AND (P-AND), and Positive OR (P-OR) structure for tQCA. These gates can be the basis of more complex circuits for ternary computation. A new methodology is presented in order to design any standard ternary logic circuit. To achieve this, we have used the combination of one positive and one negative logic gate.